Computational Chemistry: QSAR of Dental Disease Causing Streptococcus mutans Using Eugenol Derivative Compounds from Clove Essential Oil - Muliadi Muliadi; Topan Setiawan; Ike Dwi Setiani; Nur Asbirayani Limatahu; Deasy Liestianty (TECHNO: JURNAL PENELITIAN, 2023)
Research on the activity of eugenol derived compounds as antimicrobials using the qualitative structure-activity relationship (QSAR) model has been conducted. Molecular structure modeling was executed computationally using the ChemDraw Ultra 12.0 program package. Geometry optimization was performed using AM1 semi-empirical method to stabilize structure with the least energy level. Calculations of hydrophobic, electronic, and steric descriptors were done using Gaussian-09 and Marvin Sketch 64 softwares. Statistical calculations was conducted through multiple linear regression method using the IBM SPSS 25 program. Statistical analysis was carried out based on the statistical requirements of several equation models so that the best equation model was obtained. The analysis with the QSAR equation model obtained that the model 1 equation presented the best results.